DETERMINANTS OF STUDENTS UTILISATION OF COMPUTER INFORMATION RETRIEVAL SYSTEMS IN ACADEMIC LIBRARIES: EVIDENCE FROM THE UNIVERSITY OF GHANA - Boakye, G. (UDS International Journal of Development, 2016)
A number of educational institutions and libraries have established computerised information retrieval systems (CIRS) to help students to easily identify resources for their academic pursuit. The study investigates and retests the Unified Theory of Adoption and Use of Technology as a model for explaining technology (UTAUT) use among library users in the University of Ghana (UG). A questionnaire with 31 items based on the UTAUT study of Venkatesh et al (2003) and analysed on a 7 point Likert Scale was distributed to students who used the Balme Library in May, 2014. The results reveal that many students judge their ability to use the computer information retrieval system to accomplish the specified task as poor due to non-familiarity with the system. It is noted that a lot of students also doubt the ability of the system to provide the required responses they are looking for. This may be due to misconceptions from previous experiences or information gained from other people who have not been successful in using the information retrieval system. The study recommends that the Library incorporates the basic skills of interacting with the CIRS in its orientation programme to give students an acceptable perception of the CIRS. Keywords: Computerised information retrieval system, Balme Library, University of Ghana, Academic libraries, Information retrieval